Situating Microbes Within Complex Ecologies - Jose A. Cañada; Salla Sariola; Matthäus Rest (Engaging Science, Technology, and Society)
The role of microbes in society has traditionally foregrounded their pathogenic character. However, this framing is being increasingly problematised as new research has shown the complex and nuanced role they have, not only in relation to humans, but also for nonhuman animals and as part of wider and complex ecologies. In the introduction to this thematic collection, we review how such shift has featured in science and technology studies (STS) research by exploring how microbes’ characterisation goes beyond the pathogenic when situated in material, socio-economic, ecological, and historical settings. This introduction explores situatedness of microbes in STS – the key element that binds together the contributions included in this collection – and describes how recent literature has expanded beyond the pathogenic and towards complex ecologies. We conclude with a description of the articles featured in this collection and describe the way they engage with STS, microbes, and situatedness.